Action research : for beginners in classroom-based context ( A Guide for Pre-Service and In-Service teachers) - De Leon, Elmer B. (Quezon City, 2019)
This material was developed to guide beginning action researchers in the onset and outset of their research exploration experiences. It will serve as their guiding light in the process of starting, pursuing and completing the action research report. The material contains brief overview of action research that would provide information on the very nature of research. In order to set the mood and heighten motivation, this book includes purposes, significance, advantages, gains, benefits, opportunities and positive impact and implications taken from studies to ease researcher's burden in pursuing this kind of undertaking. This book would be of great help to action research beginners in their desire to pursue classroom action research which hopefully will bring great effect, positive turn-out and high impact outcome.
Keywords: Action research in education